PERSONALITY DIFFERENCES BETWEEN MALES AND FEMALES BASED ON BIG FIVE FACTORS – AN EMPIRICAL STUDY - Shah, Yashasvi (PEOPLE: International Journal of Social Sciences, 2016)
This paper takes a look at the personality traits that are given through the Big Five personality test. It studies the gender differences present in students between the age group of 18-25. The data was collected through Two-Stage stratified random sampling (N=100, Males=41, Females=59). Descriptive Analysis was done from which Females were found to score higher in the traits of Agreeableness, while Males scored higher in the traits of Adjustment, Openness, Sociability and Conscientiousness. The differences were studied at a social level and evaluated keeping in mind the previous findings. These findings help to evaluate the gender differences that occur on a trait level and give a better understanding of social systems that occur between males and females. Such an understanding can help contribute to the breaking of societal structures that occur in modern India.